2021
DOI: 10.3390/diagnostics11050848
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microcalcifications in Spiral Breast Computed Tomography with Photon-Counting Detector Is Feasible: A Specimen Study

Abstract: The primary objective of the study was to compare a spiral breast computed tomography system (SBCT) to digital breast tomosynthesis (DBT) for the detection of microcalcifications (MCs) in breast specimens. The secondary objective was to compare various reconstruction modes in SBCT. In total, 54 breast biopsy specimens were examined with mammography as a standard reference, with DBT, and with a dedicated SBCT containing a photon-counting detector. Three different reconstruction modes were applied for SBCT datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the observation of the anesthesia effect, according to the evaluation of 47 cases of spiral CT reconstruction image, there was no intubation failure during general anesthesia of endotracheal intubation, and the success rate was 100%. The detection of oxygen saturation and end expiratory carbon dioxide during anesthesia were within the normal range, indicating that the spiral CT reconstruction image before anesthesia can effectively measure and evaluate tracheal stenosis [ 14 16 ]. Spiral CT has a good representation of the complete anatomical surface of the trachea through reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…In the observation of the anesthesia effect, according to the evaluation of 47 cases of spiral CT reconstruction image, there was no intubation failure during general anesthesia of endotracheal intubation, and the success rate was 100%. The detection of oxygen saturation and end expiratory carbon dioxide during anesthesia were within the normal range, indicating that the spiral CT reconstruction image before anesthesia can effectively measure and evaluate tracheal stenosis [ 14 16 ]. Spiral CT has a good representation of the complete anatomical surface of the trachea through reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to EID-CT, photon-counting detector CT (PCD-CT) represents a fundamentally different approach for CT imaging [ 11 , 12 , 13 ]. Photon-counting detectors count the number of incoming photons and the electronic signal is proportional to the deposited energy of each photon [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, Wetzl et al 33 confirmed that the sensitivity and specificity for the detection of microcalcifications in breast specimens is at least equal or better for photon-counting breast CT compared to DBT with DM as standard reference. Therefore, with a dedicated breast CT system the visibility of microcalcifications in specimens might be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latest promising studies with further improved breast CT imaging technology for specimens 32 , 33 as well as for breast imaging, which might even be additionally improved by contrast media application 25 , more focus should be laid on breast CT. Especially in preoperative imaging dedicated breast CT might be a promising alternative to the more expensive breast MRI.…”
Section: Discussionmentioning
confidence: 99%